Arendt: ação, discurso e esfera pública - Silva, Ivonei Freitas da (2009)
This dissertation highlights Hannah Arendt's understanding of Political: deeds, speech and public sphere. In this manner, the meaning of politics is freedom, factually experienced through deeds and words, when men come forward and disclose themselves in the public sphere; i.e., politics can only surface amongst men. For being different, they need speech and deeds to make themselves understood. However, Arendt recognizes that action and speech are activities that are by themselves as futile as life itself. Deeds and words, in order to become part of the world, must be seen, heard and shared; and their only premise is the constant presence of other men. Specifically, deeds and speech are the human condition of plurality. The research was focused on Arendt's descriptions of the tradition's notions and political experiences, emphasizing that the author does not hesitate to state that recognition of human plurality and the establishment and preservation of intermediate spaces are essential conditions to political. The purposes were, on one hand, to demonstrate that Arendt's political thought is impregnated with her readings on ancient politics, conceived as an activity that arises in spaces which men set up to deal with common interests. On the other hand, to manifest that, at modern and current times, both the rise of social sphere and invasion on the field of action and speech by work and fabrication have favored the oblivion of freedom in the political sense. In short, that, to Arendt, the primary sense of politics, forgotten or obscured throughout the centuries, always finds a way to be updated, as shown in descriptions of modern revolutions, labor and popular movements and, more recently, American civil disobedience.